Ahmad Hassan dan Kehujjahan Hadis: Pemikiran Ahmad Hassan terhadap Hadis Fadailul Amal dalam Buku Soal-Jawab - Alwi, Ahmad Hanafi; Muhid, Muhid; Nurita, Andris; Fadlurrahman, Isa (NALAR, 2023)
This research examines Ahmad Hassan's thoughts regarding the fadailul amal hadith in the Soal-Jawab book. This research uses a qualitative approach. In data mining, a library research type is used by tracing various written sources to obtain other supporting data. Data analysis in this research uses the content analysis method by discussing in depth the content of information from the data collected following the research objectives and problems. The research results found that Ahmad Hassan, in principle, accepts the existence of the fadailul amal hadith. However, efforts to practice it must still be based on the criteria of maqbul hadith (sahih and hasan). As for the fadailul amal hadith, which falls within the dhaif level, Ahmad Hasan rejects its use as the sole source of law. The dhaif fadailul amal hadith only to complement the act of worship, which has a legal basis in the Koran or other maqbul hadiths.Keywords: